2013
DOI: 10.1017/s1461145713000539
|View full text |Cite
|
Sign up to set email alerts
|

Can transcranial direct current stimulation enhance outcomes from cognitive training? A randomized controlled trial in healthy participants

Abstract: Computer-administered cognitive training (CT) tasks are a common component of cognitive remediation treatments. There is growing evidence that transcranial direct current stimulation (tDCS), when given during cognitive tasks, improves performance. This randomized, controlled trial explored the potential synergistic effects of CT combined with tDCS in healthy participants. Altogether, 60 healthy participants were randomized to receive either active or sham tDCS administered during training on an adaptive CT tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
124
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(144 citation statements)
references
References 30 publications
14
124
1
5
Order By: Relevance
“…They found an improvement in performance with anodal stimulation over F4 or F3 in the highly educated subjects, but surprisingly a worsening of performance on visual n-back in the subjects with lower education and anodal stimulation over F4 (F3 in this subgroup showed no effects). Two studies showed that training on one working memory task (n-back test) during tDCS improved performance on another working memory task (digit span) after stimulation [58,59]. Consistent with other findings in the neuromodulation literature, repeated sessions (a total of 10) of anodal tDCS have shown longterm improvement in working memory performance, lasting up to 4 weeks [59,60].…”
Section: Findings In Healthy Subjects and Patientssupporting
confidence: 67%
See 2 more Smart Citations
“…They found an improvement in performance with anodal stimulation over F4 or F3 in the highly educated subjects, but surprisingly a worsening of performance on visual n-back in the subjects with lower education and anodal stimulation over F4 (F3 in this subgroup showed no effects). Two studies showed that training on one working memory task (n-back test) during tDCS improved performance on another working memory task (digit span) after stimulation [58,59]. Consistent with other findings in the neuromodulation literature, repeated sessions (a total of 10) of anodal tDCS have shown longterm improvement in working memory performance, lasting up to 4 weeks [59,60].…”
Section: Findings In Healthy Subjects and Patientssupporting
confidence: 67%
“…Montages were also different, with the most common placement situating the two electrodes over the F3 and F4 position on the international 10-20 EEG system. However, the paired electrode location differs across studies with the use of ipsilateral reference electrodes [67,80] or extra-cephalic arm electrodes [54,59,60,81]. These different montages also lead to important differences in the distribution of charge across studies.…”
Section: A Comment On Study Parameters and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an extracephalic reference electrode has also been used to influence cognitive processes in depression and healthy subjects (Wolkenstein & Plewnia, 2013;Clarke, Browning, Hammond, Notebaert & MacLeod, in press). However, this wider interelectrode distance has been found to reduce the intensity of the stimulation under the anodal electrode (Moliadze, Antal, & Paulus, 2010), and has also been associated with no clear differences between the effects of active and sham tDCS (Martin et al, 2013). All together, the research domain of combining neuromodulation with cognitive training is flourishing extremely fast, but more research is needed to explore and consider the impact of alternative and/or less investigated tDCS montages on cognition and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there have been rapid consolidation effects where group differences only begin to emerge in the minutes or hours after stimulation, or become stronger/more robust with time (e.g., Clark et al 2012;Ehsani et al 2016;Hoy et al 2014;Javadi and Cheng 2013;Penolazzi et al 2013;Reis et al 2015). Similarly, overnight consolidation has been enhanced when performance is measured the next day, despite a lack of group differences on day 1 (Koyama et al 2015;Martin et al 2014), and even cognitive training studies that failed to show immediate tDCS-related enhancements have still demonstrated greater tDCS-related retention a couple months later (Jones et al 2015;Martin et al 2013;Stephens and Berryhill 2016).…”
Section: Experimental Evidencementioning
confidence: 99%